PRACTICAL AND THEORETICAL PROBLEMS OF TRANSLATION - Axmadova Durdona Axror Qizi (Academia Science Repository, 2023)
This article reveals the history, problems and ways of solving the problems of translation. Types of translation: practical and theoretical are being discussed in order to find solutions.